The Persian Puzzle : The Conflict Between Iran and America - Pollack, Kenneth M. 1966- (New York Random House, 2004)
Pollack, a former CIA analyst and National Security Council official, analyzes the long and ongoing clash between the United States and Iran, beginning with the fall of the Shah and the seizure of the American embassy in Tehran in 1979. Pollack examines all the major events in U.S.-Iran relations--including the hostage crisis, the U.S. tilt toward Iraq during the Iran-Iraq war, the Iran-Contra scandal, military tensions in 1987 and 1988, the covert Iranian war against U.S. interests in the Persian Gulf that culminated in the 1996 Khobar Towers terrorist attack in Saudi Arabia, and recent U.S.-Iran skirmishes over Afghanistan and Iraq. He explains the strategies and motives from American and Iranian perspectives and tells how each crisis colored the thinking of both countries' leadership as they shaped and reshaped their policies over time.
Include Notes, Bibliography and Index
Keywords: United States -- Iran -- Diplomatic relations